A Survey on the Frequency of Type 1 Diabetes Mellitus and its Related Factors from 2004-2014 - Hossein Moravej; Marziyeh Rassafian; Anis Amirhakimi; Homa Ilkhanipour; Shokrollah Mazloumi- abrazgah; Negar Yazdani (Fasa University of Medical Sciences, 2020)
Background & Objective: Since epidemiological information on type1 diabetes in children can help to control it, this study aimed to determine the frequency and characteristics of type1 diabetes patients during an 11-year period. Materials & Methods: In this retrospective study, records of all 0-39 years old diabetic patients admitted to Nemazee hospital 2004-14 were reviewed. Since most new cases are admitted to this hospital, the patient's data might be a good representative of all patients in Shiraz. Gender, date of birth, age of onset and associated diseases were recorded. Data were analyzed, using SPSS 22.0.     Results: In this study, 546 diabetes patients were admitted, of which 52.4% were females. Two peak age was observed (5-9 Y/O and 10-14 Y/O). The mortality rate was 23%. Most of them had no family history of diabetes. Majority of patients (86.3%( did not have any other medical condition. Moreover, there was a significant relationship between age of onset with positive family history and mode of presentation. The frequency of diabetic patients had a rising trend during this eleven-year period. Conclusion: Incidence of type1 diabetes had a growing trend and peak age of presentation was similar to most previous studies. However, the percentage of diabetic ketoacidosis was more than that of developed countries. Therefore, people and physicians are recommended to have more information on type1 diabetes for early diagnosis to prevent further complications.